Pollution Assessment and Abatement of Ban-Ganga River at Katra Town-J&K (International Journal of Innovative Research in Engineering & Management, 2023)
The Ban Ganga is an important tributary of  river Chenab and flows thru the Katra metropolis of Jammu  and Kashmir. Katra town is a prime commercial centre for  Mata Vaishno Devi and additionally the main source of  pollutants for Ban Ganga River & Tawi River. The river has  non secular significance for Hindu Vaishnava and different  devotees. more than 10 million site visitors make the  pilgrimage each yr, and many bathes within the river to  cleanse earlier than they go away on the whole journey. Holy  Ban Ganga River, which is revered via the devotees and  locals as sacred, has been definitely became a nallah where  trash is flowing. The Ban Ganga River has been decreased to  a -metre huge drain, full of sludge, plastic and litter of  pilgrims a few pilgrims also raised worries over ecological  degradation on the Trikuta mountain variety due to massive  influx of Vaishno Devi pilgrims and alleged felling of trees,  which immediately impacts the Ban Ganga River. Locals  alleged that brisk developmental activities on the thirteen-km  track from the Katra base camp to the cave shrine have been  posing an ecological chance to the Trikuta hills and the  largest assignment before the Board turned into to hold the  ecological balance. They appealed Shrine Board as well as  the Governor to take essential initiative to smooth Ban Ganga  and feared that if emergency measures are not taken, the river  would be dead soon. since the past few decades, Katra  metropolis have skilled good-sized increase. the agricultural  areas but, tormented by inadequate infrastructure facilities,  were unable to address this swelling growth of the city  regions a chief physical infrastructure issue that desires to be  addressed within the Notified area is the inappropriate and  unhygienic disposal of waste water & sewerage via open  drains that follow the natural slope of land and its discharge,  with none remedy. family who doesn’t have septic tank  disposes their wastewater directly into drains which reveals  its ultimate way into Ban-Ganga or herbal streams placed in  the east and south east course of the town. The sewerage is  being handled manually by using sweepers in a traditional  manner and being thrown in open rain- water drains and  herbal nallahs there via growing lot of pollution in town.PHE  branch at Jammu is responsible for the distribution of water  to the town and all the villages in the Notified region, extracts  water from the Ban-Ganga Rivers, chlorinates it and then  distributes it to all the city and villages. The great of this  water is frequently inferior because of the infection of floor  and surface water that consequences from the absence of a  STP (Sewage treatment Plant) in the Notified place. the two water treatment plants have insufficient capacity to address  the growing demand for water for the horizon 12 months.  there is an absence of door-to-door waste collection practices  inside the metropolis. most effective road sweeping is being  practiced in the metropolis as a number one series of waste.  there's a scarcity of scientific waste disposal practices within  the town. stable wastes generated from households and  accommodations get disposed off alongside Katra - Reasi  road without proper treatment. This has created nuisance in  surrounding regions and makes difficult to skip from this  avenue.
Keywords: Water Quality; Water Quality Analysis; katra; Jammu & Kashmir